Performance of Hybrid Coagulation–Adsorption as a Physicochemical Separation Process for Removal of Organic Pollutants and Heavy Metals from Chemical Laboratory Wastewater - Gang Dong; Ermieza Sinin; Fahad Abu Mallouh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the performance of a hybrid coagulation and adsorption system as a physicochemical separation process for removing organic pollutants and heavy metals such as iron, manganese, and chromium from chemical laboratory wastewater, as well as to determine optimum operating conditions to improve separation efficiency. Methodology: The study used a batch experimental method consisting of coagulation followed by adsorption. Coagulation was carried out using aluminum sulfate, polyaluminum chloride, and commercial coagulants under controlled conditions of acidity, dosage, and mixing to promote particle destabilization and floc formation. The adsorption process used activated carbon and zeolite with controlled contact time and adsorbent dosage. Parameters analyzed included turbidity, total suspended solids, total dissolved solids, electrical conductivity, chemical oxygen demand, and metal concentrations. Main Findings: The coagulation process significantly improved solid–liquid separation, achieving reductions in turbidity (93.5%), Total Suspended Solids (69.13%), Total Dissolved Solids (46.95%), conductivity (72.33%), and heavy metals, including Fe (85.53%), Mn (55.84%), and Cr (43.07%). However, Chemical Oxygen Demand reduction during coagulation was limited (7.4%), indicating low removal of dissolved organic compounds. The subsequent adsorption stage enhanced Chemical Oxygen Demand removal up to 58.53% using activated carbon and 54.61% using zeolite. Novelty/Originality of this study: This study evaluates a hybrid coagulation and adsorption system as a multi-stage physicochemical separation process for complex laboratory wastewater. The novelty lies in integrating bulk separation and surface-based removal to improve overall performance and reveal process interactions affecting pollutant removal.